IMPROVING STUDENTS’ READING SKILL BY USING NARRATIVE TEXT - Luas, Tri Sofia Ningsi; Liando, Nihta V. F.; Rorimpandey, Rinny S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of the study is to discover out whether or not the utilize of Narrative Text in reading teaching can improve student’s reading skill to the third grade students. This is a quantitative research, and a reading test in multiple-choice format is use to collect data. Two narrative texts with ten multiple choice items each to consist the test. The test is using for both pretest and posttest. It was involve 35 students’ third grade of SMP MTs AL-Muhajirin in the 2023/2024 academic year. The data analysis leads to the following result: calculation of mean of pretest and posttest data was done using the formula previously mentioned. Thus, with ∑X = 168, ∑Y = 206 and n = 35, mean of pretest was 4.8, whereas mean of the posttest was 5.9. The calculation indicates that posttest mean (5.9) is bigger than that of the pretest, 4.8. In other words, it means that students reading performance in the posttest is better than their performance before the treatment. This is due to the application of Narrative Text. Standard deviation, as pointed out earlier, was calculated using raw scoring formula. Thus, with ∑X2 = 860, pretest mean 24.5, and n = 35, the standard deviation of pretest was 0,7; with ∑Y2 = 1264, mean = 36.1, and n = 35, the standard deviation of posttest was 1.0. The result indicates that students reading performance in the pretest or before the treatment is more heterogeneous than their performance after the treatment